2023
DOI: 10.1186/s12864-023-09587-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, metabolomic, and transcriptomic reveal metabolic pathway alterations in Gymnocypris przewalskii due to cold exposure

Sijia Liu,
Fei Tian,
Delin Qi
et al.

Abstract: Teleost fish have evolved various adaptations that allow them to tolerate cold water conditions. However, the underlying mechanism of this adaptation is poorly understood in Tibetan Plateau fish. RNA-seq combined with liquid chromatography‒mass spectrometry (LC‒MS/MS) metabolomics was used to investigate the physiological responses of a Tibetan Plateau-specific teleost, Gymnocypris przewalskii, under cold conditions. The 8-month G. przewalskii juvenile fish were exposed to cold (4 ℃, cold acclimation, CA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 109 publications
0
0
0
Order By: Relevance
“…Environmental stress can accelerate fat breakdown, providing free fatty acids as a primary source of energy for fish metabolism [67]. Studies have shown that fatty acid anabolism and catabolism, including fatty acid elongation, fatty acid degradation, unsaturated fatty acid biosynthesis, and fatty acid β-oxidation, are activated in several tissues, including intestine, hepatopancreas, and muscle, in Gymnocypris przewalskii from Qinghai Lake under cold stress, suggesting that the naked carp dependently utilize fatty acids as an energy primary source [68]. Another study demonstrated that under crowding stress, immune indicators in hybrid sturgeon (♀Acipenser baerii × ♂Acipenser schrenckii) did not show significant changes.…”
Section: Energy Metabolism Disordermentioning
confidence: 99%
“…Environmental stress can accelerate fat breakdown, providing free fatty acids as a primary source of energy for fish metabolism [67]. Studies have shown that fatty acid anabolism and catabolism, including fatty acid elongation, fatty acid degradation, unsaturated fatty acid biosynthesis, and fatty acid β-oxidation, are activated in several tissues, including intestine, hepatopancreas, and muscle, in Gymnocypris przewalskii from Qinghai Lake under cold stress, suggesting that the naked carp dependently utilize fatty acids as an energy primary source [68]. Another study demonstrated that under crowding stress, immune indicators in hybrid sturgeon (♀Acipenser baerii × ♂Acipenser schrenckii) did not show significant changes.…”
Section: Energy Metabolism Disordermentioning
confidence: 99%